Автотрассовый газоанализатор - Devyatko, G. A.; Kuchmenko, V. A.; Latsis, S. A.; Orlov, V. A.; Partyshev, V. O.; Podolskiy, V. Ya. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The air pollution sources along populated area motorways are defined. The principle of working, development and ways of selectivity improvement of the alignment gas analyser electrochemical sensors are shown. The operation alignment gas analyser results in the ecological monitoring system of the pollution level in the air along motor roads in Kyiv are presented.